IMPROVING STUDENTS’ PARTICIPATION IN LISTENING COMPREHENSION CLASS USING SIMON SAYS GAME - Puspita, Winda; Ikhsanudin, Ikhsanudin; Rosnija, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to improve students’ participation in listening comprehension class using Simon Says Game. This research was conducted on the eight grade students of MTs Negeri 1 Pontianak in academic year 2017/2018. The subject was class VIII E that consisted of 40 students. The researcher conducted a classroom action research which was done in two cycles. The data were collected using observation, measurement, and recording technique. The tools of data collection were scoring rubric, observation checklist, field notes, and handy camera. The result of data analysis showed that Simon Says Game was able to improve students’ participation. The students could give and act out the instructions well. It was shown that the students’ mean scores in giving the instructions improved from 1.68 (cycle 1) to 2.15 (cycle 2). Meanwhile, the mean score of acting out the instructions was improved from 1.83 (cycle 1) to 2.28 (cycle 2). It can be concluded that the students’ participation in listening comprehension class improved. In other words, this technique can help the students give instructions and act out the instructions correctly. Keywords: Participation, Listening Comprehension Class, Simon Says Game